The Design and Construction of A Dynamic Multi-Sensor and Multi-Storage Data Logger for Weather Parameters - Wahyuni, Retno Tri; Subagiyo, Heri; Huda, Amirul (LPPM Universitas Muhammadiyah Riau, 2023)
The Data Logger is an electronic device designed to automatically and continuously store data. Data loggers are widely used in various fields, including the storage of weather parameter data. Generally, a data logger consists of sensor devices, a processor, and storage media. This paper discusses the design of a dynamic data logger that allows the selection of sensor input types and storage media such as an SD card or a cloud database. The data logger comprises hardware devices, including five weather parameter sensors, a processor and a communication module using ESP32, a timing system using RTC, and local storage media in the form of an SD card. Additionally, there is a computer-based user interface built using Visual Basic. The connection between the user interface application and the data logger hardware is established using serial communication. Overall system testing results indicate that all features of the data logger system have operated well.